Kontribusi Sistem Informasi Manajemen dalam Mendukung Strategi Bisnis Modern - Sopia Ariska; Irwan Padli Nasution (JOURNAL SAINS STUDENT RESEARCH, 2025)
The development of modern business is marked by intense competition, rapid market changes, and the growing need for fast, data-driven decision-making. In this context, Management Information Systems (MIS) play a crucial role as strategic tools that support the formulation and implementation of business strategies. This article aims to theoretically examine the contribution of MIS to business strategy success in the digital era. Using a descriptive qualitative method through literature review, the discussion focuses on the role of MIS in enhancing operational efficiency, gaining competitive advantage, and supporting strategic decision-making. The findings indicate that MIS is not merely a technological or administrative tool, but an integral part of business processes that facilitates cross-departmental data integration, increases information transparency, and drives data-based innovation. Therefore, the optimal use of MIS has become a critical requirement for organizations striving to survive and thrive amid digital disruption.